Teaching Islamic values through traditional stories - Gayatri, Satya; Firmansyah, Okta; Pratiwi, Dyani Prades (Diksi, 2023)
This research is motivated by the lack of appreciation to explore the values of the Minangkabau story, even though the report also conveys a religious message. By using the close reading technique, this paper interprets the various moral messages contained in 11 Minangkabau stories, namely Anak Mudo, Limau Anyuik, The Honest Child, Batu Manangih, Boncah Tangkuluak, Carito Bukik Balacan, Kuciang jo Harimau, Rumah Raksasa, Urang Kayo Sampilik, Kawan nan Setia,, and Tupai jo Limbek. From the analysis of this story, moral messages were found, such as honesty, respect for mothers, humility, and mutual help. This morality is seen to be by Islamic character, based on the two measuring tools Gus Dur regarding the principle/consistency and sincerity of the message content, and also based on the reality of the Minangkabau people's customs intertwined with Islam. This story articulates the Minangkabau community's ability to cultivate themselves by adhering to traditions and Islam.Keywords: Morality, Value, Message, Minangkabau Story, Islam